Efavirenz-loaded polymeric nanocapsules: Formulation, development, and validation of an RP-UHPLC-DAD method for drug quantification, determination of encapsulation efficiency, stability study, and dissolution profile - Amanda Martinez Lyra, Juliana Parente Menezes Ribeiro, Jessica Mendes Nadal, Sinvaldo Baglie, Traudi Klein, Andressa Novatski, Paulo Vitor Farago (Journal of Applied Pharmaceutical Science, 2021)
This study aims at preparing efavirenz (EFV)-loaded polymeric nanocapsules and carrying out the analytical method development and validation in order to provide a suitable tool for evaluating these formulations in terms of encapsulation efficiency, stability, and dissolution profile. The nanoformulations were obtained by the interfacial deposition of preformed polymer(s). The analytical method was specific, linear (r² = 0.9990), precise, accurate, and robust from 1.0 to 50.0 μg/ml and demonstrated a drug retention time of 1.6 minutes. The mean encapsulated drug content was higher than 99.0%. All formulations showed stability problems at room temperature since the values of pH, particle size, and polydispersity index increased, while the zeta potential intensified its negative value after 60 days of storage. However, the storage in the refrigerator was able to prevent this process in most of the investigated formulations. Concerning the drug loading, all EFV-loaded nanocapsules based on poly(ε-caprolactone) and [poly(ethylene glycol) 6000] were statistically stable after 60 days of storage. The nanoencapsulation was responsible for prolonging the drug release for both EFV-loaded formulations by anomalous transport.
Keywords: Chromatography validation, drug release, nonnucleoside reverse transcriptase inhibitor, physicochemical stability testing, poly(ε-caprolactone).